A realtime Runner Help Me mobile application using geolocation technique / Nurul Amierah Abd Rahman - Abd Rahman, Nurul Amierah (2019)
In this era, people seems to live in a hectic lifestyle which lead to lack of time. Therefore, runner service is an answer to help them. Runner is someone who is responsible to run errand on behalf of someone who needs and willingly to pay them. However, there is no platform for runner to advertise their service and let people know about their service. As for customer, some of them does not know the existence of runner service. Nevertheless, certain people realize of the existence of runner service but they do not know the appropriate way to find the runner. They will search only via internet or social media which is the probability to find them is very low. Once they found, they need to contact the runner personally which is make the process harder since the one who needs the runner probably has time limitation. Moreover, customer does not know the exact amount that they need to prepare before or after they request the runner due to they need to wait after the runner finish their task first. Afterward, the runner will pick random number or based on the job without having specific algorithm to charge the customer. It will be inappropriate since the runner monopolize the price without customer concern. Besides, the personal runner cannot guarantee the safety of customer items since customer cannot track them and it will build lack of trust in between of customer and the runner. The objective of the system is to identify the user requirements of Runner Help Me mobilebased application system. Next, to design and develop a Runner Help Me mobile-based application system. Then, to evaluate usability and functionality of the proposed system. As for the methodology, agile method is the superlative methodology for this project. This method is suitable due to it is easy to follow the flow and it allowing change for every phase. The expected outcome is the proposed system that is Runner Help Me mobilebased application protoype is produced.